Essentials of criminalistics - Peckley, Miller F. (Quezon City: Wiseman's Books Trading, Inc., 2016)
--The crime laboratory --Forensic Science --Different divisions of criminalistics --Print types --Timeline --Validity of fingerprint --Errors in identification or processing --Forensic ballistics --Bullet comparisons --Cartridge --Gunpowder residue analysis --tool markers and other impressions --History of police photography --History of the camera --Forensic Chemistry --The history of forensic chemistry --Toxicology --Question document examination --Scope of document examination -- Book used in North America --Lie detection and interrogation --Forensic medicine.
Chapter I. Introduction --II, Different divisions of criminalistics --III. Commonly ask questions.
Includes glossary and bibliography
Keywords: Forensic sciences